A Study of Middle Age Sanskrit Poṣadha Palm-leaf Manual - Bajracharya, Birat Raj (Historical Journal, 2023)
The Poṣadha, or observing of eight Buddhist precepts by lay and monastic people in Buddhism starts inthe lifetime of Buddha. With the growth of time, many Buddhist sects developed and they developed their Poṣadha methods (I.-Tsing, 1896). Among them is the tradition of the Sanskrit Mahayana monks. This article is about a palm-leaf manuscript [RAS Hudgson MS 70] from the Hudgson collection which is now in the South Asian society collection. This Poṣadha manual written by a novice has great significance as it takes us back to the time when the monks following Sanskrit tradition were still functioning. Interestingly this Poṣadha text is based largely on the Mahayana context and has very little Sravakayana influence. Directions for forming puṣpamaṇḍala has significant difference which hasn't been revealed before. This Vrata manual can be looked at as the initial ritualistic development of a now surviving Sanskrit Buddhism, this is Newar Buddhism.